Biological characteristics and prognosis of acute myeloid leukemia in elderly patients - Chen, Zhe; Ding, Lina; Yu, Jieni; Jin, Jing; Zhang, Zhijian; Fu, Jiaping; Hong, Pan; Fu, Leihua (Frontiers in Genetics, 2025)
BackgroundOur study aimed to investigate the effects of chromosomal aberrations and genetic mutations of elderly individuals diagnosed with AML and determine its prognostic significance.MethodsWe retrospectively collected data over nearly 7 years from our hospital, encompassing 90 cases of elderly AML patients. Baseline information of patients was gathered and followed up, and statistical analysis was conducted using SPSS 25.0.ResultsAmong the 90 elderly non-M3 AML patients, 56 (62.2%) exhibited multiple gene mutations, with 9 (10%) patients displaying five or more gene mutations. The incidence of NPM1 mutation was significantly higher in patients with normal karyotypes compared to those with abnormal karyotypes (P = 0.001). Patients with FLT3, ASXL1, or TP53 mutations displayed lower rates of CR compared to wild-type counterparts. Kaplan-Meier analysis revealed that TET2 mutation (P = 0.0474), FLT3-ITD mutation (P = 0.0364), TP53 mutation (P = 0.0031), and 17p abnormality (P = 0.00285) were predictive of shorter OS. TP53 mutations (P = 0.0440), 17p abnormalities (P = 0.0272), 7q abnormalities (P = 0.0174), and complex karyotypes (P = 0.0447) were associated with shorter RFS.ConclusionOur findings suggest that elderly AML patients exhibit distinctive genetic profiles, and favorable prognosis genes do not seem to apply to elderly AML patients.